2017
DOI: 10.1002/adem.201700048
|View full text |Cite
|
Sign up to set email alerts
|

A Combinatorial Approach for Assessing the Magnetic Properties of High Entropy Alloys: Role of Cr in AlCoxCr1–xFeNi

Abstract: A combinatorial assessment of composition‐microstructure‐magnetic property relationships in magnetic high entropy AlCoxCr1‐xFeNi alloy (0 ≤ x ≤ 1) system has been carried out using compositionally graded alloys fabricated via laser additive manufacturing. At one end, the AlCoFeNi composition (x = 1) consisted of equiaxed B2 grains, exhibiting very early stages of phase separation (only compositional partitioning) into Ni–Al rich and Fe–Co rich regions within grains of the B2 phase. At the other extreme, the Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(58 citation statements)
references
References 47 publications
1
52
0
Order By: Relevance
“…al on FeCoCrNi alloys. [7][8][9] The multiple similarly sized atoms mixed in relatively equiatomic amounts in these alloys lead to a 2 nd order magnetic transition, which is broadened due to the distributed exchange interactions arising from the disorder, [10][11][12][13][14] and allows Tc tuning and control of the refrigeration capacity, which leads to a broader transition range than seen in traditional alloys. This is a novel approach to increasing the refrigeration capacity of a magnetocaloric material that does not rely on physical processing (ball milling, cold rolling, etc) to broaden the temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…al on FeCoCrNi alloys. [7][8][9] The multiple similarly sized atoms mixed in relatively equiatomic amounts in these alloys lead to a 2 nd order magnetic transition, which is broadened due to the distributed exchange interactions arising from the disorder, [10][11][12][13][14] and allows Tc tuning and control of the refrigeration capacity, which leads to a broader transition range than seen in traditional alloys. This is a novel approach to increasing the refrigeration capacity of a magnetocaloric material that does not rely on physical processing (ball milling, cold rolling, etc) to broaden the temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…The work combined experiments with DFT calculations to determine the balance between the surface and interfacial energies of the observed phases, which is particularly useful in elucidating the complex architectures of HEAs containing more than four phases. Since greater compositional diversity and structural complexity have been the tendency, we conclude the relationship between elements and phase numbers of HEAs based on the large numbers of reports, which is illustrated in Figure 9,13,25,63–75. It shows that the compositions of HEAs reach up to eight elements, and the number of phases achieves four.…”
Section: Phase Structure Of Heasmentioning
confidence: 84%
“…Research has shown that HEAs could get fine soft magnetic properties with high magnetization and low coercivity by selecting suitable elements and compositions. Banerjee et al explored the role of Cr in AlCo x Cr 1− x FeNi (0 ≤ x ≤ 1) to study the magnetic properties 70. The hysteresis loops for AlCo x Cr 1− x FeNi are illustrated in Figure a.…”
Section: Property Adjusting Of Phase Engineered Heasmentioning
confidence: 99%
See 2 more Smart Citations